Analysis of the Cochrane Review: Exercise-Based Cardiac Rehabilitation for Coronary Heart Disease. Cochrane Database Syst Rev. 2016;1:CD001800 - Carvalheira-dos-Santos, Rita; Delgado, Ricardo-Manuel; Ferreira-dos-Santos, Guilherme; Vaz-Carneiro, António (Acta Médica Portuguesa, 2019)
Coronary heart disease is the single most common cause of death globally, accounting for one-third of all deaths. However, with falling coronary heart disease mortality rates, an increasing number of people live with the disease and may need support to manage their symptoms and prognosis. A complex intervention that may involve a variety of therapies, cardiac rehabilitation includes exercise, risk factor education, behavioral change, psychological support, and strategies that are aimed at targeting traditional risk factors for cardiovascular disease. Cardiac rehabilitation is an essential part of contemporary heart disease care and is considered a priority in countries with a high prevalence of coronary heart disease. This Cochrane systematic review constitutes an update of a Cochrane review published in 2011, having identified 16 new trials (3872 participants), predominantly post-myocardial infarction and post-revascularization patients. Therefore, it included 63 randomized trials looking at the effectiveness and cost-effectiveness of exercise-based cardiac rehabilitation in patients with coronary heart disease. The quality of the evidence ranged from low to moderate. The main results highlight the effect of cardiac rehabilitation, in comparison with absence of physical exercise, in the reduction in cardiovascular mortality, with no reduction, however, in total mortality. The overall risk of hospital admissions was reduced with cardiac rehabilitation but there was no significant impact on the risk of myocardial infarction, coronary artery bypass graft or percutaneous coronary intervention. This paper aims to summarize and discuss the main results and conclusions of this systematic review, as well as its implications for the daily clinical practice.